IT-Based Cost and Inventory System for Small Industry - Abd Halim, Chairel Azezee; Sh Ahmad, Prof. Madya Dr. Sh Salleh (Research Progress in Mechanical and Manufacturing Engineering, 2024)
IT-based has emerged as one of the most in-demand method as the internet becomes an integral part of people’s daily life. Small industries are looking for the simplest method of managing and monitoring product cost and inventory remotely, outside of a physical office and store. By proposing Mini IT-based cot and inventory system for small industry, the study aims to develop a system which has an ability to estimate product costs and assess the effects of significant material price increase on overall product costs. The proposed system also includes an inventory management process which is intended to help small industries manage their inventory efficiently, keep track of product stock, and respond wisely to changes in material availability. Users can input changes to material prices, and the system will automatically update the costs of the final product. This enables industries to assess the financial impact and make necessary modifications to pricing or sourcing strategies. The small IT-based cost and inventory system supports accurate and effective inventory management and cost analysis. It eliminates manual calculations, lowers the possibility of mistakes, and offers real-time access to product costs and product inventory.